Receipt of the actions of the Agronomic Institute of Pernambuco by farmers of São Bento do Una, Pernambuco, Brazil - Lopes, Mízia Fabiana Moreira Barbosa; Costa, Jakes Halan de Queiroz; Santos, Tânia Marta Carvalho dos; Lima, Conceição Maria Dias; Lopes, José Cândido Barbosa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Food production is being widely discussed worldwide, both in terms of increasing productivity to meet the needs of the growing population and also in terms of the quality of these foods. Small farms are responsible for producing for the majority of the population and for their own family subsistence. The objective of this study was to reveal the importance of Technical Assistance and Rural Extension (ATER) actions for small farmers to remain in the countryside, due to their role in food production and job creation. The study was carried out in the municipality of São Bento do Una/Pernambuco, which receives technical assistance from the Agronomic Institute of Pernambuco (IPA). Interviews with semi-structured script were carried out with family farmers and IPA technicians, in addition to direct observations covering qualitative and quantitative data. There was a need for greater government attention, with more public policies so that services, projects and programs can be better developed. In this sense, family farmers need more effective ATER actions that bring better working and development conditions to the rural areas of the municipality.